Banking and economic development : some lessons of history - Cameron, Rondo E. (New York : Oxford University Press, 1972)
The problem of financing economic development in contemporary underdeveloped and developing countries
Includes bibliographical references.
obn 23/01/2019
Loans
Keywords: Industrialization; Banks and banking; Economic development